2009
DOI: 10.7551/mitpress/9780262013468.001.0001
|View full text |Cite
|
Sign up to set email alerts
|

Chips and Change

Abstract: How the chip industry has responded to a series of crises over the past twenty-five years, often reinventing itself and shifting the basis for global competitive advantage. For decades the semiconductor industry has been a driver of global economic growth and social change. Semiconductors, particularly the microchips essential to most electronic devices, have transformed computing, communications, entertainment, and industry. In Chips and Change, Clair Brown and Greg Linden trace the industry ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…The qualitative grounded theory approach provides opportunities to create new understandings rather than a method to provide rigorous, empirical testing of existing theories, an area where various quantitative methods may be more useful. While others have studied China and India in the context the globalization of R&D [33,35,39] and the globalization of the IC sector specifically [10], there has not been a comparative analysis of the evolution of Indian and Chinese IC design that incorporates opening up the "black box" of the firms to investigate how design is organized in the MNCs and domestic firms in order to conceptualize how each country's industry structure and skills have evolved over time.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The qualitative grounded theory approach provides opportunities to create new understandings rather than a method to provide rigorous, empirical testing of existing theories, an area where various quantitative methods may be more useful. While others have studied China and India in the context the globalization of R&D [33,35,39] and the globalization of the IC sector specifically [10], there has not been a comparative analysis of the evolution of Indian and Chinese IC design that incorporates opening up the "black box" of the firms to investigate how design is organized in the MNCs and domestic firms in order to conceptualize how each country's industry structure and skills have evolved over time.…”
Section: Methodsmentioning
confidence: 99%
“…In the IC design industry, the accumulated evidence is that both China and India have increased their global market share, activities and technical capabilities in this area [10,20,38,17,18]. 1 IC design has been a success in each country despite predictions of substantial differences in sectoral success and specialization of each country [5,8] assumed to be due to the generally acknowledged different development paths outlined above.…”
Section: Literature Reviewmentioning
confidence: 96%
See 2 more Smart Citations
“…2 It is increasingly recognized that the rapid growth of India's economy is attributable to this kind of business-service trade utilizing time zone differences. 3 Related to these phenomena, Marjit (2007) examined the role of international time zone differences in a vertically integrated Ricardian framework. It has been shown that time zone differences emerge as an independent driving force of international trade besides taste, technology and resource endowment.…”
Section: Introductionmentioning
confidence: 99%